2019
DOI: 10.1097/ccm.0000000000003545
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Cardiopulmonary Resuscitation: One-Year Survival and Neurobehavioral Outcome Among Infants and Children With In-Hospital Cardiac Arrest*

Abstract: Objective: To describe neurobehavioral outcomes and investigate factors associated with survival and survival with good neurobehavioral outcome one year after in-hospital cardiac arrest for children who received extracorporeal cardiopulmonary resuscitation (ECPR). Design: Secondary analysis of the Therapeutic Hypothermia after Pediatric Cardiac Arrest In-Hospital (THAPCA-IH) trial. Setting: 37 PICUs in the United States, Canada and the United Kingdom. Patients: Children (n=147) resuscitated with ECPR following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 46 publications
0
25
0
Order By: Relevance
“…In a multicenter randomized trial of therapeutic hypothermia after IHCA, only 30.5% of patients who received ECPR for IHCA had good neurobehavioral outcomes at 12 months of age. 51 In patients who received ECPR, therapeutic hypothermia, compared with normothermia, tended to be associated with lower survival with good neurobehavioral outcome at 1 year. 51 Single-center analyses lack consistency in reported measures of neurologic function/status yet demonstrate favorable neurologic outcomes for the majority of survivors at follow-up (median range, 25-52 months).…”
Section: Expertise and Equipment (Class Iib Loe [Level Of Evidence]mentioning
confidence: 89%
See 1 more Smart Citation
“…In a multicenter randomized trial of therapeutic hypothermia after IHCA, only 30.5% of patients who received ECPR for IHCA had good neurobehavioral outcomes at 12 months of age. 51 In patients who received ECPR, therapeutic hypothermia, compared with normothermia, tended to be associated with lower survival with good neurobehavioral outcome at 1 year. 51 Single-center analyses lack consistency in reported measures of neurologic function/status yet demonstrate favorable neurologic outcomes for the majority of survivors at follow-up (median range, 25-52 months).…”
Section: Expertise and Equipment (Class Iib Loe [Level Of Evidence]mentioning
confidence: 89%
“…[46][47][48] Our understanding of neurologic function after resuscitation with ECPR consists of single-center follow-up analyses 49,50 and the results of a randomized prospective trial of therapeutic hypothermia after IHCA. 51 There is insufficient information about neurologic complications and outcomes (ie, hemorrhagic/ischemic stroke, seizure) associated with the use of ECPR in infants and children. In a multicenter randomized trial of therapeutic hypothermia after IHCA, only 30.5% of patients who received ECPR for IHCA had good neurobehavioral outcomes at 12 months of age.…”
Section: Expertise and Equipment (Class Iib Loe [Level Of Evidence]mentioning
confidence: 99%
“…During ECPR, an extracorporeal circuit is established to maintain vital organ perfusion until potentially reversible causes of cardiac arrest are identified and treated. Survival to hospital discharge after ECPR is about 40% [1,2]; however, long-term cognitive and neurologic outcomes among survivors are largely unknown [3][4][5][6]. Knowledge regarding these outcomes is important for clinical decision-making, counselling parents, and planning rehabilitation and educational services during recovery.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that about a third of children receiving ECPR in the context of the THAPCA-IH trial survived with good neurobehavioral function at one year based on caregiver responses to the VABS-II [3]. Benefits of using a caregiver-report measure included the ability to collect data in-person or by telephone, and to obtain a retrospective assessment of each child's pre-arrest functional status.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, patient’s core body temperature of 33 to 35 °C is maintained for 24–48 h [ 8 ]. Therapeutic hypothermia when compared with normothermia after ECPR is associated with lesser survival with good neurobehavioural outcome at 1-year follow-up [ 23 ].…”
Section: Post-ecpr Managementmentioning
confidence: 99%